2005
DOI: 10.1111/j.1360-0443.2004.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Response consistency in young adolescents’ drug use self‐reports: a recanting rate analysis

Abstract: M. (2005). Response consistency in young adolescents' drug use self-reports: a recanting rate analysis. Addiction, 100(2)(2), 189-196. DOI: 10.1111189-196. DOI: 10. /j.1360189-196. DOI: 10. -0443.2004 Published in: AddictionQueen's University Belfast -Research Portal: Link to publication record in Queen's University Belfast Research Portal General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
94
3
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 26 publications
9
94
3
4
Order By: Relevance
“…Inconsistent reporting has also been shown for other stigmatized behaviors such as drug use (Percy, McAlister, Higgins, McCrystal, & Thornton, 2005). We extend this research by examining consistency in reporting of self-harm regardless of suicidal intent, and by examining various characteristics associated with discrepant reporting.…”
Section: Comparison With Previous Researchmentioning
confidence: 78%
“…Inconsistent reporting has also been shown for other stigmatized behaviors such as drug use (Percy, McAlister, Higgins, McCrystal, & Thornton, 2005). We extend this research by examining consistency in reporting of self-harm regardless of suicidal intent, and by examining various characteristics associated with discrepant reporting.…”
Section: Comparison With Previous Researchmentioning
confidence: 78%
“…In contrast, those who engage in more deviant behavior (such as delinquency or crime) may be more consistent in their self-reports of drug use because they have less ambivalence about their behavior. Percy et al (2005) found some evidence for this as those who report serious offending were less likely to recant their earlier reported drug use than those who did not report offending. They concluded that the social costs of reporting drug use may be comparably low for them while for others drug use may represent the most serious offense committed and thus disclosure has greater social cost.…”
Section: Consistency Of Reports Across Timementioning
confidence: 99%
“…Some suggest that respondents change their definition of substance use as they age (Engles et al, 1997;Percy et al, 2005). For example, having a puff of marijuana at age 12 might be considered drug use during adolescence (and indeed the wording of questions on most surveys would suggest that it is) while this amount of use might be construed as nonuse as an adult.…”
Section: Consistency Of Reports Across Timementioning
confidence: 99%
See 2 more Smart Citations